Mechanical Ventilation during Chest Compressions – The Impact on Tidal Volumes. - Johannes Wittig; Simon Orlob; Christoph Hobisch; Daniel Auinger; Gabriel Honnef; Tobias Fellinger; Robin Ristl; Otmar Schindler; Philipp Metnitz; Georg Feigl; Gerhard Prause (AGN Journal, 2022)
Research question Chest compressions and ventilation are essentials in cardiopulmonary resuscitation (CPR). [1] During CPR, excessive ventilation frequencies are observed, while blood gas analyses indicate that hypoventilation is prevalent. [2,3] Transport ventilators can control ventilation frequency. The impact of chest compressions on tidal volumes remains uncertain. This study was previously published and investigated whether transport ventilators can generate tidal volumes adequate for gas exchange during continuous chest compressions. [4] Methodology Three transport ventilators – ‘MEDUMAT Standard2’, ‘Oxylog 3000 plus’, ‘Monnal T60’ – were investigated in a randomized cross-over study. Six Thiel-embalmed cadavers served as CPR models. They received volume-controlled ventilation with tidal volumes of 6 ml/kg ideal predicted bodyweight (IPBW) and continuous chest compressions. Airflow, airway pressure, and esophageal pressure were recorded. Derived volumes and their deviation from preset volumes were compared and analyzed in a linear mixed model. Results 715 ventilations were included. Median preset tidal volume was 390 (40, [290; 410]) ml. Median inspiratory tidal volume was 275 (68, [47; 464]) ml, corresponding to 4.75 (1.2, [0.7; 7.6]) ml/kg PIBW. Median deviation from preset value was −21.2 (19.6, [−87.9; 25.8]) %. For ‘MEDUMAT Standard2’ median deviation was −31.5 (16.6, [−56.5; −14.8]) %, −22.7 (22.1, [−70; −12.3]) % for ‘Oxylog 3000 plus’ and −8.3 (20.5, [−87.9; 25.8]) % for ‘Monnal T60’. Linear mixed model estimates were −31 [95%-CI: −38.9; −23] % (p < 0.0001), −30.6 [95%-CI: −38.6; −22.6] % (p < 0.0001), −14.5 [95%-CI: −22.5; −6.5] % (p = 0.0004) for ‘MEDUMAT Standard2’, ‘Oxylog 3000 plus’ and ‘Monnal T60’ respectively. Interpretation Transport ventilators can deliver tidal volumes that contribute to gas exchange during continuous chest compressions. However, tidal volumes are significantly reduced. Therefore, tidal volumes should be continuously monitored during CPR. [1] Soar, Jasmeet et al. “European Resuscitation Council Guidelines 2021: Adult advanced life support.” Resuscitation vol. 161 (2021): 115-151. doi:10.1016/j.resuscitation.2021.02.010 [2] Aufderheide, Tom P et al. “Hyperventilation-induced hypotension during cardiopulmonary resuscitation.” Circulation vol. 109,16 (2004): 1960-5. doi:10.1161/01.CIR.0000126594.79136.61 [3] Prause, Gerhard et al. “Hyperventilation is uncommon during cardio-pulmonary resuscitation: A preliminary observational study.” Resuscitation vol. 162 (2021): 257-258. doi:10.1016/j.resuscitation.2021.03.008 [4] Orlob, Simon et al. “Reliability of mechanical ventilation during continuous chest compressions: a crossover study of transport ventilators in a human cadaver model of CPR.” Scandinavian journal of trauma, resuscitation and emergency medicine vol. 29,1 102. 28 Jul. 2021, doi:10.1186/s13049-021-00921-2